Detecção de erosão dental utilizando análise de espalhamento de luz coerente - speckle - Koshoji, Nelson Hideyoshi (2014)
Dental erosion is a non-carious cervical lesion that is related to progressive tooth loss through its contact with chemicals that dissolve the enamel hydroxyapatite crystals. Currently, it is a highly prevalent condition among individuals of all ages. The loss of the structure of this tissue causes changes in the roughness of the surface. The objective of this work is to develop a methodology to identify and quantify this injury, in a non-invasively and non-destructive way, with low cost and executed in real time by analyzing the coherent light scattering patterns, called speckle. It was used 32 samples of bovine incisors and they were divided into 4 groups with different times of acid etching. Half of each sample was protected and then immersed in Coke (pH ≅ 2.5) for 10, 20, 30 and 40 min, twice daily and for 7 consecutive days. Each sample has two areas: half healthy and half eroded. After the challenge, the samples were submitted to speckle analysis to find the relative differences between the two regions in each group. It was found 10 min with 18% 20 min with 24% 30 min with 38% and 40 min with 44% of relative difference. After this analysis, we performed also a Knoop hardness test in order to compare methods. There was a linear trend between the methods with coefficient r = 0.80. The speckle image is proportional to the attack time, has a strong correlation and a good agreement with the Knoop hardness test.